2015
DOI: 10.3390/nu8010003
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Associations between Empirically-Derived Dietary Patterns and Indicators of Disease Risk among University Students

Abstract: The transition from adolescence to adulthood is a unique period during which lifelong dietary habits are shaped. Dietary patterns (DPs) among young adults attending college have not been adequately described, and associations between DPs and indicators of disease risk are not well understood in this age group. Dietary data were collected from undergraduates participating in the Tufts Longitudinal Health Study (TLHS; 1998–2007) by Food Frequency Questionnaire (FFQ; n = 1323). DPs were derived using principal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 94 publications
5
33
1
3
Order By: Relevance
“…The results of Del Piero et al [52] showed that the diet of Argentine university students moves away from a pattern of healthy eating since it is based primarily on processed, industrialized, and micronutrient-poor products. Similar to what has been reported by Pastor et al [53] in Spain, Whatnall et al [49] in Australia, and Blondin et al [54] in the US, patterns that include processed foods explained most of the total variance (22.2%, 16.8%, and 10.3% respectively); we found a "dairy & cereals" pattern that contained a high proportion of processed breakfast cereals. Thus, food patterns of university students may be similar, independent of the continent where they live.…”
Section: Discussionsupporting
confidence: 90%
“…The results of Del Piero et al [52] showed that the diet of Argentine university students moves away from a pattern of healthy eating since it is based primarily on processed, industrialized, and micronutrient-poor products. Similar to what has been reported by Pastor et al [53] in Spain, Whatnall et al [49] in Australia, and Blondin et al [54] in the US, patterns that include processed foods explained most of the total variance (22.2%, 16.8%, and 10.3% respectively); we found a "dairy & cereals" pattern that contained a high proportion of processed breakfast cereals. Thus, food patterns of university students may be similar, independent of the continent where they live.…”
Section: Discussionsupporting
confidence: 90%
“…Late adolescence and early adulthood period has been reported as indicative in relation to weight changes and adoption of poor dietary and exercise patterns (9); numerous studies from US have confirmed that freshman years among university students are critical in weight gain and behavioral patterns that may contribute to overweight and obesity (10)(11)(12). Weight gain in freshman college students and perceived health among European undergraduate has proven to follow the same pattern, but with a more pronounced perception of overweight and obesity among female students (8), even within other age groups (13,14) (gender-sensitive dimorphism).…”
Section: Introductionmentioning
confidence: 99%
“…Some pieces of research have identified lifestyle patterns associated to specific phenotypes and obesity in several population groups [34,35] and contributed to unravel the consequences that different diets may have on health [2,11,35,36,37,38]. …”
Section: Discussionmentioning
confidence: 99%